Knowledge and Practices about Malaria Among the Sandstone Quarry Workers in Jodhpur District, Rajasthan - Yadav, S P; Mathur, Murli L (Annals of Arid Zone, 2016)
Malaria_ is a common parasitic disease transmitted through mosquitoes. It affects health as well as economic condition of victims. Following rains •. water is accumulated in quarries which become breeding grounds for mosquitoes round the year. This study w'as conducted on the sandstone quarry workers for deter~ining their level of awareness and practices about malaria. It revealed that majority (79.2%) of the sandstone quarry workers were below the age of 40 years and 71.1% were illiterate. In all 33% of respondents were aware of the cause of malaria as mosquito bite. Awareness about causation of disease increased with the literacy status, being 22.5% in illiterates and 88.5% in those with middle school or higher education. Nearly 40% of the respondents attributed high fever with chills and rigor as the most important symptom of malaria. Less than 49% of workers knew that mosquito bred in water while only 22.2% knew mosquito breeding could be prevented. This knowledge was more prevalent among educated workers as compared to illiterates. Our study has shown that the awareness about the cause and practices of prevention of malaria were just fair among the sandstone quarry workers and needs to be strengthened.